PENERAPAN TEORI PERMAINAN DALAM STRATEGI PEMASARAN PRODUK BAN SEPEDA MOTOR DI FMIPA USU - Charles Simamora; Elly Rosmaini; Normalina Napitupulu (Universitas Sumatera Utara, 2013)
Game Theory is a mathematical model that is used in situations of conflict or competition between the various interests face each other as competitors. The goal is to obtain the optimal strategy for each player. In game theory, there are two types of optimal strategies, the pure strategy and mixed strategy. The author use linear programming to obtain the optimal mixed strategy and use QM 2.0 to solve linear programming problems. In this research, the author apply game theory in competition motorcycle tire, the IRC, Federal, and Swallow. The research was conducted at the Faculty of Mathematics and Natural Sciences and using primary data. In other words, this research produced the preferences and perceptions of consumers for each tires.